Leveraging Blockchain for a living, trustable curriculum vitae - Ferreira da Silva, C.; Paulo Rupino da Cunha; Almeida, P. (18th European Mediterranean & Middle Eastern Conference on Information Systems, 2021)
The Blockchain technology provides a secure and distributed ledger. This single source of truth enables parties to validate information regarding transactions. It is precisely this characteristic that brings added value to the recruitment area, since, currently, the process of validating the training and career information presented by the talents is a manual and time-consuming process. In this field, the objective is to store data about talent, recruiters, and endorsements in a safe and transparent way, conveying confidence to all stakeholders in the recruitment process. We present a Digital Career Logbook (DCL), a system for collecting, registering and safeguarding professional knowledge and career events based on blockchain and smart contracts. The DCL implemented system privileges open-source software and low-cost resources. For this, we selected Infura, an Ethereum blockchain API, and Polygon, a protocol and a framework for building and connecting Ethereum-compatible blockchain networks. It relies on the Proof-of-Stake consensus algorithm and aggregates scalable solutions on Ethereum. The DCL user interface integrates a MetaMask browser extension, that enables users to store their Ethereum accounts including private keys securely inside the browser. When a frontend application requires interaction with the smart contract, it requests MetaMask to sign a transaction and MetaMask will forward the request to the user to confirm.